2016
DOI: 10.1590/s2179-975x1516
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter input and electrical conductivity may change density of Phylloicus sp. (Trichoptera: Calamoceratidae) in a Brazilian savannah stream

Abstract: Aim Shredders are generally not abundant in tropical streams, and there is considerable evidence suggesting that the food supply drives this pattern in headwaters. The aim of this study was to assess the effect of variation in the availability of food resources, over one year, on the density of Phylloicus sp. (Trichoptera: Calamoceratidae), which is one of the main shredders in Neotropical headwaters. Methods We measured the relative importance of organic matter in terms of vertical input (VI) and benthic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…, Leite et al . ). We have demonstrated that these differences can affect leaf decomposition rates and, consequently, ecosystem functioning of savannah streams.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…, Leite et al . ). We have demonstrated that these differences can affect leaf decomposition rates and, consequently, ecosystem functioning of savannah streams.…”
Section: Resultsmentioning
confidence: 97%
“…, Leite et al . ). Our study supports the idea that the size and structural characteristics (quality) of litter are important factors that affect decomposer communities and litter breakdown rates in savannah streams.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Higher values of electrical conductivity result from increased ion concentrations and indicate increased nutrient concentrations in the water (Leite et al 2016). Thus, higher nutrient values may be associated with the decomposition of allochthonous organic matter (mainly leaves) in containers (Gessner et al 1999).…”
Section: Discussionmentioning
confidence: 99%